Lanthanum oxide-promoted cobalt catalyst supported on mesoporous alumina for syngas production via methane dry reforming - Tran, Ngoc Thang (2022)
Methane dry reforming reaction (MDR) has recently emerged as a promising multipurpose approach for converting two greenhouse gasses, included carbon dioxide (CO2) and methane (CH4), into valuable feedstock for downstream petrochemical processes. At present, there is still a challenge in developing the highly stable and active catalysts for MDR reaction as well as better resistance to carbon deposition. Though the mesoporous alumina supported Co-based catalysts have recently appeared to be the potential catalysts. However, the common starting materials for preparing these wellordered mesoporous catalyst supports are organic precursors and anhydrous ethanol which are quite expensive and harmful to the environment. Therefore, in this study, mesoporous alumina (Al2O3), fabricated using a cheap and available inorganic aluminium precursor in binary water-ethanol solvent, was implemented as support for cobalt catalyst. This investigation aimed to design an effective cobalt-based catalyst system for MDR reaction, which overcomes coke-related deactivation barriers. The promotional effect of La2O3 on the physicochemical features of Al2O3 supported cobalt catalyst and its catalytic performance were also elucidated. The catalyst evaluations in MDR reaction were conducted for 10%Co/Al2O3 and La2O3-promoted 10%Co/Al2O3 catalysts (La loading was in 1% – 8%) in a fixed-bed reactor at temperature range of 923 – 1073 K and partial pressure of individual reactant from 10 to 40 kPa. The Al2O3 support has BET surface area of 173.4 m2 g-1 and cobalt nanoparticles were finely dispersed on the support with desired crystallite size ranged from 5.2 - 9.2 nm. The strong interaction of CoO and Al2O3 phases was confirmed by the presence of cobalt-aluminate spinel and the textural structure of catalysts was stable with reaction temperature. The promotion behavior of La2O3 facilitated H2-reduction by providing higher electron density and enhanced oxygen vacancy in 10%Co/Al2O3. The addition of La2O3 could reduce the apparent activation energy of CH4 consumption; hence, increasing CH4 conversion up to 93.7% at 1073 K. Lanthanum dioxycarbonate transitional phase formed in situ during MDR was accountable for mitigating deposited carbon via redox cycle for 17-30% relying on reaction temperature. Additionally, the oxygen vacancy degree increased to 73.3% with La2O3 promotion. 5%La loading was an optimal promoter content for reactant conversions as well as yield of H2 and CO. 5%La-10%Co/Al2O3 also exhibited the highest resistance to carbon deposition owing to the basic nature, redox feature of La2O3 dopant. The MDR reaction over 5%La-10%Co/Al2O3 catalyst was convinced to follow an associative adsorption mode of CH4 and CO2 on dual or different sites of active particles and the catalyst exhibited a good stability during 48 h reaction at 1023 K. The resulting H2/CO ratios of 0.84-0.98 are suitable for Fischer-Tropsch reaction in downstream to generate liquid hydrocarbon fuels. As a result, the employment of mesoporous alumina support and La2O3 promoter efficiently boosted the Co activity in MDR reaction along with suppressing the carbon deposition on the catalyst surface.